2016
DOI: 10.1084/jem.20160334
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and treatment of the Staphylococcus aureus reservoir in vivo

Abstract: Kubes et al. show that methicillin-resistant Staphylococcus aureus (MRSA) survive and proliferate inside Kupffer cells. Intracellular MRSA is resistant to neutrophil-killing and antibiotics treatment and, when released into the circulation, can infect other organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
267
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(274 citation statements)
references
References 33 publications
6
267
1
Order By: Relevance
“…S. aureus required 4–8 h to secrete sufficient AT, as AT-dependent platelet aggregation was only observed at 8 h while direct administration of AT caused instantaneous aggregation. Remarkably, this timeframe coincided directly with the time it takes for S. aureus to escape from Kupffer cells (Surewaard et al, 2016). Blocking AT reduced the staphylococcal burden inside the liver as well as the kidney.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…S. aureus required 4–8 h to secrete sufficient AT, as AT-dependent platelet aggregation was only observed at 8 h while direct administration of AT caused instantaneous aggregation. Remarkably, this timeframe coincided directly with the time it takes for S. aureus to escape from Kupffer cells (Surewaard et al, 2016). Blocking AT reduced the staphylococcal burden inside the liver as well as the kidney.…”
Section: Discussionmentioning
confidence: 64%
“…We previously reported that some S. aureus survive and even replicate inside Kupffer cells and subsequently disseminate to kidneys (Surewaard et al, 2016). S. aureusΔhla did not survive as effectively inside the liver as the WT strain (Figure 5C) and dissemination to kidneys trended towards a lower bacterial burden (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that S. aureus that survive within phagocytes serve as a reservoir of infection during systemic disease, resulting in increased bacterial outgrowth and reduced host survival [183]. Hla- induced changes in intracellular signaling causes increased β1-integrin surface expression and subsequent phagocytosis, allowing bacteria to escape the extracellular-bactericidal functions of mast cells [184, 185].…”
Section: Cellular Effects Of Toxin Actionmentioning
confidence: 99%
“…For liver imaging, mice were anesthetized and cannulated as described above, and intravital imaging was performed as previously described (19,20).…”
Section: C3 -/-mentioning
confidence: 99%